Strategy to Improve Communication Between Farmers and Companies in The Boiler Chicken Supply Chain - Eileen Nathania; Mirwan Surya Perdhana (Return : Study of Management, Economic and Bussines, 2023)
Communication problems are still the main thing in carrying out the company's strategy. This is a challenge for farmers to build good relationships and relationships with partners who are partners in cooperation in the livestock sector. There is no research related to the relationship between companies and companies in Central Java and qualitative research, so it is necessary to conduct this research So this study also analyzes what is carried out where companies must have character, trust (with mutual trust), open communication, be fair and dare to take risks. Therefore, this study aims to fill the gap / gap of previous research related to the topics previously described. The research method used is qualitative research method. This research approach uses phenomenological methods. The study was conducted in the close farm area of broiler chickens spread across Central Java and samples of 7 chicken coops to represent the Central Java area. Based on the experience of 7 Saorce Person, the majority of decisions to cooperate with companies are due to direct interaction communication from the company (Interactive Communication). Communication is carried out formally at the cooperation agreement stage at the beginning before joining the partnership. When there is a problem during the cooperation period, the majority of farmers understand and seek solutions together with the company. The beliefs of each resource person vary based on each individual's experience. There are resource persons who believe in the company because of the company's image, trust the company because of closeness or Personal Bound with Area managers / Supervisors / Staff.